KONTRIBUSI KEPALA SEKOLAH DALAM PENGEMBANGAN BUDAYA SEKOLAH DI SMK NEGERI 1 MEULABOH - Novi Zulfiati; Cut Zahri Harun; Niswanto Niswanto (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2021)
The contribution of a principal in the development of school culture is very important in establishing students’ character. The aims of this research were to find out the principal's programs in developing school culture, the implementation, the supervision, and the obstacles faced by the principal during the implementation. This research used a descriptive method with a qualitative approach. The data collection was conducted through interviews, observations, and documentation studies. The subjects of this research were the principal, teachers, students, and school committee. The results of this research showed that (1) the principal’s programs in developing school culture was designed to strengthen its vision and mission through students character building, developing an entrepreneurial culture according to students department; (2) the implementation of principal’s program in developing school culture involved all school members, establishing social and emotional relationships through meetings, providing the good role model, and developing an entrepreneurial culture that carried out through the internalization of entrepreneurial values in school culture; (3) the supervision was carried out together with school members. The principal supervised directly to monitor the process of implementing school culture development; and (4) the obstacles faced by the principal were the school’s facilities and infrastructures that were optimally used, the absence of a reward and punishment system, and the difficulty of developing students’ commitment which affected students’ discipline and religious values, such as violating school rules. Abstrak Kontribusi kepala sekolah dalam pengembangan budaya sekolah sangatlah penting dalam pembentukan karakter peserta didik. Tujuan penelitian ini untuk mengetahui: program kepala sekolah dalam pengembangan budaya sekolah, pelaksanaan, pengawasan, dan hambatan-hambatan kepala sekolah dalam pengembangan budaya sekolah. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Pengumpulan data diperoleh dari wawancara, observasi, dan studi dokumentasi. Subjek penelitian kepala sekolah, guru-guru, siswa, dan komite. Hasil penelitian yaitu: (1) Program kepala sekolah dalam pengembangan budaya sekolah yaitu Menguatkan visi misi Pengembangan budaya sekolah menyangkut dengan pembinaan akhlak/karakter, pengembangan budaya kewirausahaan sesuai dengan jurusan; (2) Pelaksanaan program kepala sekolah dalam pengembangan budaya yaitu melakukan kerjasama dengan seluruh perangkat sekolah, membangun hubungan sosial dan emosional melalui rapat,memberikan contoh teladan, Pengembangan budaya wirausaha dilaksanakan melalui internalisasi nilai-nilai wirausaha dalam kultur sekolah; (3) Pengawasan dilakukan bersama dengan perangkat sekolah. kepala sekolah melakukan pengawasan secara langsung dalam memantau proses pelaksanaan pengembangan budaya sekolah; dan (4) Hambatan-hambatan yang dihadapi kepala sekolah yaitu: penggunaan sarana dan prasarana yang belum optimal, tidak adanya sistem reward dan punishment, Sulitnya membangun komitmen peserta didik sehingga berimbas pada nilai kedisiplinan dan religius seperti, melanggar aturan sekolah. Kata Kunci: Kontribusi, Kepala sekolah, Budaya sekolah